2012
DOI: 10.1371/journal.pone.0049555
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Beginning of Time: Circadian Rhythms in Metabolism Precede Rhythms in Clock Gene Expression in Mouse Embryonic Stem Cells

Abstract: The appearance, progression, and potential role for circadian rhythms during early development have previously focused mainly on the suprachiasmatic nucleus (SCN) and peri- and postnatal expression of canonical clock genes. More recently, gene expression studies in embryonic stem cells have shown that some clock genes are expressed in undifferentiated cells; however rhythmicity was only established when cells are directed toward a neural fate. These studies also concluded that a functional clock is not present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…This is in line with the emergence of circadian rhythmicity during differentiation of embryonic stem cells that do not possess a functional circadian clock 49, 53. Clock genes are expressed in ES cells, however, and the emergence of a functional clock system is closely linked to differentiation 49, 50, 51, 53, but these factors may have additional functions in those cells. The intimate link between clock proteins and the cell cycle was discussed above, and stem cell proliferation may be regulated by these factors.…”
Section: Future Perspectivessupporting
confidence: 63%
See 1 more Smart Citation
“…This is in line with the emergence of circadian rhythmicity during differentiation of embryonic stem cells that do not possess a functional circadian clock 49, 53. Clock genes are expressed in ES cells, however, and the emergence of a functional clock system is closely linked to differentiation 49, 50, 51, 53, but these factors may have additional functions in those cells. The intimate link between clock proteins and the cell cycle was discussed above, and stem cell proliferation may be regulated by these factors.…”
Section: Future Perspectivessupporting
confidence: 63%
“…In murine pluripotent stem cells, circadian rhythms were shown to be established when differentiation is induced upon withdrawal of leukemia inhibitor factor (LIF) (passive) or by the addition of retinoic acid (active) 49, 50, 51. When reversing differentiation through reprogramming 52, the clock is switched off again 49 (Fig 3A), which indicates that the (in)activation of the diurnal clock is a reversible process that is intensively linked with the differentiation state of a cell.…”
Section: The Circadian Clock In Stem Cell‐derived Cellsmentioning
confidence: 99%
“…Thus, cell-intrinsic rhythms of circadian gene expression are probably present at the very earliest stages of development. It has even been suggested that circadian rhythms of energy consumption in ES cells might briefly precede the emergence of canonical circadian transcriptional oscillations (Paulose et al, 2012).…”
Section: From Stem Cells To Developmentmentioning
confidence: 99%
“…ESCs were previously considered not to possess any intrinsic timekeeping because although clock gene transcription factors such as BMAL1 are expressed, their levels do not exhibit circadian cycles until after differentiation. Paulose et al, however, report a self-sustained circadian rhythm in ESC uptake of 2-deoxyglucose prior to, and following, differentiation (102). Similar to the findings in erythrocytes, this suggests that circadian rhythms in metabolism (in this case glucose utilization) may persist in the absence of gene expression (cycling or otherwise), but does not satisfactorily address whether transcriptional cycles (when they are present) may run independently from metabolic oscillations, or are coupled with them.…”
Section: Cellular Clocksmentioning
confidence: 99%
“…Based on the examples above, however, it seems reasonable to expect an impending flood of observations detailing how metabolic cues can directly regulate the activity of circadian-relevant transcription factors and cellular rhythms in general. Moreover, since the stability and localization of identified clock proteins is regulated post-translationally, via phosphorylation/ubiquitination, through enzyme systems that appear to be conserved throughout the eukaryotes; it is not clear that the mRNA levels of the ''clock gene'' transcription factors actually need to oscillate for them to fulfill their role, merely that sufficient mRNA be present at the appropriate circadian phase to facilitate translation of nascent polypeptide chains (102). Clearly, however, as with cycles of transcriptional activation/repression, the degradation of these transcription factors and their mRNAs will increase the signal-to-noise ratio within this molecular circuit and thereby impart directionality to the cycle.…”
mentioning
confidence: 99%